2015
DOI: 10.1111/isqu.12181
|View full text |Cite
|
Sign up to set email alerts
|

Sovereign Credit and the Fate of Leaders: Reassessing the “Democratic Advantage”

Abstract: In this article, we contend that the "democratic advantage" literature (i) exaggerates the potential political backlash from credit downgrades in democracies; and (ii) overlooks the importance of sovereign credit to nondemocratic leaders. We argue that nondemocratic regimes receive a higher marginal political benefit from credit compared to democratic regimes. Consequently, changes in credit prices or credit access affect nondemocratic leaders' tenure more than democratic leaders' tenure. To test this argument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(23 citation statements)
references
References 65 publications
1
20
0
Order By: Relevance
“…This component of our argument is consistent with Wintrobe, whose political economy approach to dictators' allocation decisions demonstrates that fiscal policy favors small, elite groups in non-democratic regimes (Wintrobe, 1998). There are numerous 8 DiGiuseppe and Shea (2015) use a similar argument to argue that changes in creditworthiness will affect the political survival of non-democracies leaders more than democratic leaders. examples that demonstrate this fiscal logic, including the Marcos regime in the Philippines, military regimes in Latin America in the 1970s, the Duvaliers in Haiti, and the South African apartheid system (Wintrobe, 1998).…”
Section: Argumentsupporting
confidence: 77%
See 1 more Smart Citation
“…This component of our argument is consistent with Wintrobe, whose political economy approach to dictators' allocation decisions demonstrates that fiscal policy favors small, elite groups in non-democratic regimes (Wintrobe, 1998). There are numerous 8 DiGiuseppe and Shea (2015) use a similar argument to argue that changes in creditworthiness will affect the political survival of non-democracies leaders more than democratic leaders. examples that demonstrate this fiscal logic, including the Marcos regime in the Philippines, military regimes in Latin America in the 1970s, the Duvaliers in Haiti, and the South African apartheid system (Wintrobe, 1998).…”
Section: Argumentsupporting
confidence: 77%
“… DiGiuseppe and Shea () use a similar argument to argue that changes in creditworthiness will affect the political survival of non‐democracies leaders more than democratic leaders. …”
mentioning
confidence: 99%
“…This work has spurred a sub-literature on how political regime type a↵ects the political consequences of defaulting and politicians' willingness to repay (e.g. Beaulieu et al, 2012;DiGiuseppe and Shea, 2015;Saiegh, 2005). More recently authors have highlighted the political incentives that democratic politicians may have not to repay (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…More recently authors have highlighted the political incentives that democratic politicians may have not to repay (e.g. DiGiuseppe and Shea, 2015;Walter, 2013). Still others focus on the importance of elections (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, democracies can borrow money at a cheaper rate because they send a credible signal to loaners that they will service their debt responsibly (Dincecco 2009;North and Weingast 1989;Schultz and Weingast 2003). However, as recent studies have demonstrated that there is little difference between the abilities of democracies and autocracies to borrow money, such a democratic advantage holds only under particular conditions (Archer et al 2007;DiGiuseppe and Shea 2015;Saiegh 2005). 26 For these conflicting reports, I do not exclude this political variable in the first place.…”
Section: Mids 20mentioning
confidence: 99%